Eosinophilic esophagitis: current perspectives from diagnosis to management. Issue 1 (28th July 2016) - Moawad, Fouad J.; Cheng, Edaire; Schoepfer, Alain; Al‐Haddad, Sahar; Bellizzi, Andrew M.; Dawson, Heather; El‐Zimaity, Hala; Guindi, Maha; Penagini, Roberto; Safrooneva, Ekaterina; Chehade, Mirna
Abstract : Eosinophilic esophagitis (EoE) is a chronic antigen‐mediated immune disease of the esophagus characterized by symptoms related to esophageal dysfunction, as well as significant esophageal eosinophilia. Although dense eosinophilia is the hallmark of EoE, other characteristic histologic features have been described that may help distinguish EoE from other competing diagnoses, although none are specific to EoE. One or more foods and, at times, environmental allergens trigger EoE. Left untreated, esophageal inflammation in EoE may lead to esophageal remodeling and stricture formation. Symptoms in EoE vary with age, as they relate to the progression of the disease from an inflammatory to a fibrostenotic phenotype over time. There are currently no U.S. Food and Drug Administration–approved therapies for EoE. Current options include various dietary‐restriction therapies, topical corticosteroids, and esophageal dilations. Several emerging therapies aiming at restoring the esophageal barrier function or targeting various inflammatory cells or their mediators are under investigation.